Can robotic gastric bypass be considered a valid alternative to laparoscopy? Our early experience and literature review - Pavone, Giovanna; Pacilli, Mario; Gerundo, Alberto; Quazzico, Andrea; Ambrosi, Antonio; Tartaglia, Nicola (Frontiers in Surgery, 2024)
BACKGROUND: Robotic bariatric surgery is an alternative to laparoscopy. It gives the surgeon an accurate threedimensional view, allowing complex maneuvers while maintaining full control of the theater. HYPOTESIS: We report our experience with this innovative surgery compared with laparoscopy during Rouxen-Y gastric bypass, to demonstrate its safety and feasibility. The aim of this study is to evaluate if there are any differences between the robotic and laparoscopic techniques.MATERIALS AND METHODS: Our study retrospectively identified 153 consecutive obese patients who underwent either laparoscopic or robotic gastric bypass procedures over a 2-year period in our Department of Medical and Surgical Sciences, University of Foggia. Demographics, Operative Time, Conversion, length of stray and mortality data were collected and compared in the two groups of patient: 82 underwent laparoscopic procedure and 71 robotic.RESULTS: We analyzed 153 patients underwent gastric bypass with a mean age of 42,58 years of which 74 were female; 71 treated with robotic approach and 82 with laparoscopic approach. The mean operative time was 224,75 ± 10.4 min for Robotic Gastric Bypass (RGB) (including docking time) and 101,22 min for Laparoscopic Gastric Bypass (LGB) (p<0,05) which is statistically significant. The median length of stay was 4,1 days for RGB group and 3,9 day for LGB group (p=0,89). Only one conversion to laparoscopy in RGB group. We observed only 1 case of post-operative complication: 1 endoluminal bleeding in laparoscopic group underwent to medical treatment. No mortality was observed in either group. CONCLUSION: Statistic analysis seems to favor robotic approach that had a less incidence of complication but longer operative time. In our experience laparoscopic approach remain a technique with a major haptic feedback than robotic approach and more confident for the surgeon.